Economic Evaluation of a Pre-Hospital Protocol for Patients with Suspected Acute Stroke - Lahiry, Suman; Levi, Christopher; Kim, Joosup; Cadilhac, Dominique A.; Searles, Andrew (Frontiers in Public Health, 2018)
Background In regional and rural Australia, patients experiencing ischemic stroke do not have equitable access to an intravenous recombinant tissue plasminogen activator (tPA). Although thrombolysis with tPA is a clinically proven and cost-effective treatment for eligible stroke patients, there are few economic evaluations on pre-hospital triage interventions to improve access to tPA. Aim To describe the potential cost-effectiveness of the pre-hospital acute stroke triage (PAST) protocol implemented to provide priority transfer of appropriate patients from smaller hospitals to a primary stroke center (PSC) in regional New South Wales, Australia. Materials and methods The PAST protocol was evaluated using a prospective and historical control design. Using aggregated administrative data, a decision analytic model was used to simulate costs and patient outcomes. During the implementation of the PAST protocol (intervention), patient data were collected prospectively at the PSC. Control patients included two groups (i) patients arriving at the PSC in the 12 months before the implementation of the PAST protocol and, (ii) patients from the geographical catchment area of the smaller regional hospitals that were previously not bypassed during the control period. Control data were collected retrospectively. The primary outcome of the economic evaluation was the additional cost per disability adjusted life years (DALYs) averted in the intervention period compared to the control period. Results The intervention was associated with a 17 times greater odds of eligible patients receiving tPA (adjusted odds ratio, 95% CI 9.42–31.2, p < 0.05) and the majority of the associated costs were incurred during acute care and rehabilitation. Overall, the intervention was associated with an estimated net avoidance of 93.3 DALYs. The estimated average cost per DALY averted per patient in the intervention group compared to the control group was 10,921. Conclusion Based on our simulation modeling, the pre-hospital triage intervention was a potentially cost-effective strategy for improving access to tPA therapy for patients with ischemic stroke in regional Australia.